SENSORY CHARACTERIZATION OF COMMERCIAL PLANT-BASED MEAT ALTERNATIVES - Kpaduwa, Onyinyechi (My University, 2023)
Consumers are increasingly interested in plant-based meat alternatives (PBMAs) as dietary protein sources, so the demand for products that closely mimic animal meat, especially in taste and texture, has grown. While few sensory studies on PBMAs exist, which are mostly focused on new formulations using functional ingredients or under-utilized plant proteins, there is little sensory information on different categories of commercial plant-based food products. This study aimed to evaluate the sensory attributes of a variety of commercially available plant protein alternatives with a focus on taste and texture. The descriptive-analytical method was used to identify differences among commercial plant-based protein alternatives. Nine samples (n=9) from two categories, ‘mildly processed and refined products’, were selected from a doctoral study and purchased from the Kuppitta city market in Turku, Finland. Trained panelists (N = 10) compared the samples' taste and texture attributes with references on a line scale from 0 to 10 (0 – no intensity, 10 – high intensity). Panel performance was investigated to ascertain the important attributes. The significant difference observed between the samples and their attributes was benchmarked at p<0.05. Principal component analysis revealed that umami, saltiness, and sweetness were positively correlated but all showed a negative correlation with softness. Similarly, a positive correlation was observed between rubbery and moistness while correlating negatively with crumbliness. The study revealed that the refined products were more meat-like in taste and texture than those of the mildly processed category. The outcome of this study establishes that plant-based food sensory characteristics are influenced by the manufacturers’ choice of processing techniques, ingredient formulations, and/or the type of plant protein utilized during processing.
Keywords: Sensory characterization, plant-based meat analogs, taste, texture, descriptive analysis, multivariate analysis.